The optimal inflation rate and firm-level productivity growth - Henning Weber (Kiel Institute for the World Economy (IfW), 2012)
Empirical data show that firms tend to improve their ranking in the productivity distribution over time. A stickyprice model with firm-level productivity growth fits this data and predicts that the optimal long-run inflation rate is positive and between 1.5% and 2% per year. In contrast, the standard sticky-price model cannot fit this data and predicts optimal long-run inflation near zero. Despite positive long-run inflation, the Taylor principle ensures determinacy in the model with firm-level productivity growth, and optimal inflation stabilization policies are standard. In a two-sector extension of this model, the optimal long-run inflation rate weights the sector with the stickier prices more heavily.
Keywords: E31; E32; E52; E61; 330; optimal monetary policy; indeterminacy; heterogenous firms; firm entry and exit; Optimale Inflationsrate; Produktivität; Unternehmenswachstum; Preisrigidität; Markteintritt; Marktaustritt; Theorie